2021
DOI: 10.1002/clt2.12005
|View full text |Cite
|
Sign up to set email alerts
|

Current pet ownership modifies the adverse association between long‐term ambient air pollution exposure and childhood asthma

Abstract: Background Recent studies suggest that household endotoxin and allergens can modify the impact of air pollutants on development of asthma; however, epidemiological evidence is limited and conflicting. Objectives To investigate whether pet ownership modified the association between ambient air pollution and asthma in children. Methods We conducted a population‐based cross‐sectional study, the Seven Northeast Cities Study in China and recruited a total of 59,754 children from 94 schools during 2012–2013. Long‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A previous study conducted in China found that pet ownership was associated with an increased risk of respiratory morbidities, such as chronic bronchitis and asthma ( 58 ). However, recent updates suggest that pet ownership could potentially alleviate the detrimental effects of prolonged air pollution on childhood asthma ( 59 ). Early-life exposure to dogs and cats might be protective against developing allergies and asthma in children ( 60 ) Nonetheless, the relationship between pet ownership and allergies/allergic rhinitis is complex and not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted in China found that pet ownership was associated with an increased risk of respiratory morbidities, such as chronic bronchitis and asthma ( 58 ). However, recent updates suggest that pet ownership could potentially alleviate the detrimental effects of prolonged air pollution on childhood asthma ( 59 ). Early-life exposure to dogs and cats might be protective against developing allergies and asthma in children ( 60 ) Nonetheless, the relationship between pet ownership and allergies/allergic rhinitis is complex and not fully understood.…”
Section: Discussionmentioning
confidence: 99%